1998
DOI: 10.1038/sj.onc.1201690
|View full text |Cite
|
Sign up to set email alerts
|

TP53 DNA contact mutations are selectively associated with allelic loss and have a strong clinical impact in head and neck cancer

Abstract: Recent studies have suggested that di erent mutation types within the core domain of the tumour suppressor protein p53, i.e. DNA contact mutations and structural mutations, confer di erent biological properties. We have analysed in 86 head and neck squamous cell carcinomas (HNSCC), whether these p53 mutation types have a di erential clinical impact. Thirty-seven missense mutations were identi®ed. Thirteen of these (36%) were DNA contact mutations, occurring in the L3 loop, in the H2 loop sheet helix motif, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 11 publications
3
85
1
4
Order By: Relevance
“…The viral oncogene E6 binds and inactivates p53, while in tumors without HPV involvement TP53 gene is mostly inactivated by mutation, often accompanied by allelic loss (Ahomadegbe et al, 1995;Erber et al, 1998;Tabor et al, 2001;Braakhuis et al, 2004b). In a previous study, we showed that a significant difference in allelic loss frequency at 17p was observed between HPV-positive and -negative tumors, as determined by microsatellite markers (Braakhuis et al, 2004b).…”
Section: Discussionmentioning
confidence: 77%
“…The viral oncogene E6 binds and inactivates p53, while in tumors without HPV involvement TP53 gene is mostly inactivated by mutation, often accompanied by allelic loss (Ahomadegbe et al, 1995;Erber et al, 1998;Tabor et al, 2001;Braakhuis et al, 2004b). In a previous study, we showed that a significant difference in allelic loss frequency at 17p was observed between HPV-positive and -negative tumors, as determined by microsatellite markers (Braakhuis et al, 2004b).…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, mutations in these codons are now regarded as contact mutations which might acquire stronger carcinogenic ability. [45][46][47] In the present case, a point mutation was found at one of the CpG hot spots, codon 248 in exon 7 which is located in the L3-loop of the p53 protein. The establishment of an NK leukemia cell line with a contact mutation may serve as a good model for further study of p53-associated leukemogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown previously that p53 transgenic mice with a dominant-negative p53 mutation are highly susceptible to carcinogen-induced lung adenoma/adenocarcinoma, uterine sarcoma, and colon adenocarcinoma (9)(10)(11)(12). Mutation in the p53 gene is also commonly seen in SCCs of oral mucosa (13)(14)(15)(16). Abnormal staining of p53 protein is a frequent finding (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%